Motion of the Cerebellar Tonsils in the Foramen Magnum during the Cardiac Cycle - Cousins, J.; Haughton, V. (American Journal of Neuroradiology, 2009)
Tonsil motion was measured with cine MR imaging in patients clinically suspected of having Chiari I malformation. Cardiac-gated sagittal 2D fast imaging employing steady-state acquisition (2D FIESTA) was performed in 11 patients with a Chiari I malformation and in 6 subjects without tonsil ectopia. Tonsil motion was measured through the cardiac cycle with a pixel-shift program designed for that purpose. Tonsil displacements in patients with Chiari I and those with normal cerebellar tonsils were compared. In patients with Chiari I and subjects with normal cerebellar tonsils, 2D FIESTA showed small-amplitude tonsil movement in cephalad and caudad directions during the cardiac cycle. The average total magnitude of motion was 0.43 mm in subjects with normal tonsils (controls) and 0.57 mm in patients with Chiari malformations, 33% greater than that in controls. Tonsil motion was 0.61 mm in the patients with syringomyelia and 0.50 mm in those without it (22% difference).